How to lead with digital media effectively? A literature-based analysis of media in a E-leadership context - Kraft, Michael Hans Gino (Journal of Economic Development, Environment and People, 2019)
In many companies and industries, the use of digital media is an essential prerequisite for leaders to communicate and collaborate with employees in spatially separated situations. From this point of view, leaders must use electronic media such as e-mail, telephone conferences and virtual platforms effectively for organizational purposes. Under this premise, this paper summarizes the arguments and counterarguments within the scientific discussion on the use of digital media in the context of E-leadership. The main purpose of the research is to uncover the different relevance of electronic media in the light of virtual team leadership. Therefore, this research represents a literature analysis of E-leadership media in virtual context. The review took place between April 2019 and June 2019. The paper provides first indications of the different relevance of electronic media for the leadership of virtual teams and identifies difficulties in the implementation and prioritization of electronic media. The study confirms and proves that, in addition to conceptual challenges in the area of E-leadership, the effective use of electronic media such as social media instruments can also be optimized by a better awareness of the use of media among leaders and employees.